AMSAL IN THE QUR’AN - Rifa'in, Aswar; Latif, Abdul (Ma'had Aly As'adiyah Sengkang, 2024)
Jalaluddin al-Suyuti also divides the Amsal al-Qur'an into two parts: First, Amsal Musarahah Bih. Second, Amsal Kaminah. Meanwhile, Mannaa' Khalil al-Qattan adds another type called Amsal Mursal. According to al-Qurtubi, Amsal al-Qur'an is divided into four forms: First: Amsal al-Qasas. Second: Amsal lil Hal. Third: Amsal al-Wasfi. Fourth: Amsal al-I'tibar.